2014
DOI: 10.4103/0253-7184.132431
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of tertiary syphilis complicated with aortic aneurysm in this era of early use of highly effective antibiotics

Abstract: This 35-year-old man presented with history of hemoptysis and breathlessness on exertion of 3 months duration. Examination revealed feeble left radial, brachial and carotid pulses. Chest radiograph showed a superior mediastinal mass and contrast enhanced computed tomography chest showed a large aortic arch with mass and compression effects. Endosonographic examination was suggestive of aortic aneurysm. During further evaluation, serum Venereal Disease Research Laboratory test was found to be positive in titers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Late symptomatic syphilis is a rare systemic disease that can affect the skin, the mucous membranes, the circulatory system, the nervous system and the skeletal system. The incidence of tertiary syphilis decreases significantly with the introduction of penicillin in its early stage, but new cases of this disease are still being reported [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Late symptomatic syphilis is a rare systemic disease that can affect the skin, the mucous membranes, the circulatory system, the nervous system and the skeletal system. The incidence of tertiary syphilis decreases significantly with the introduction of penicillin in its early stage, but new cases of this disease are still being reported [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ,…”
Section: Discussionmentioning
confidence: 99%
“…Late syphilis involving the internal organs (Lues visceralis) most often affects the cardiovascular system [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], mainly as aortitis that can develop aneurysms. Gummas can also be located in the lungs, the liver, the pancreas, the digestive tract and even the adrenal glands [ 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given his lack of obvious risk factors for the development of arterial thrombosis, an alternative cause of syphilis infection was suspected. Approximately ⅓ of patients with untreated syphilis present with tertiary syphilis 10-30 years following initial exposure, and while rare, thrombosis of the aorta has been reported in syphilitic aortitis, a sequela of the tertiary disease [9]. Recent research studying Treponema pallidum has revealed that it is an invasive bacteria with the ability to readily cross-endothelial barriers through its ability to interact with, and activate platelets [10].…”
Section: Discussionmentioning
confidence: 99%